The manifestations of the legend and its symbols in the novel simorgh by Mohammad Dib - Salhi, Amel; BOUNAB, Abdelhak Mansour (Journal of Human Sciences, 2020)
This study seeks to reveal the manifestations of the legend and its symbols in the novel Simorgh by Mohammad Dib. We find that the writer was inspired by the legendary heritage and used it in the folds of his romantic discourse, relying on the mechanisms of the legendary techniques to clarify this use and show his legendary references and symbols and the manner of the use of these legendary elements and their presence in the novel. They were based in their artistic construction and their coherent and cohesive general structure on the legend of Simorgh / the Phoenix in addition to several Eastern and Western legends, joining the structure of the novel to form a basic essence in the process of reading and analysis of this romantic discourse. This use allowed him to express various questions related to the reality and the human self in an artistic way, opening the door of creativity, embodying his visions and presenting his reflections and ideas.